PATOGENISITAS JAMUR ENTOMOPATOGEN Lecanicillium lecanii (DEUTEROMYCOTINA; HYPHOMYCETES) TERHADAP Bemisia tabaci (G.) SEBAGAI VEKTOR VIRUS COWPEA MILD MOTTLE VIRUS (CMMV) PADA TANAMAN KEDELAI - Gepi M Putra; Tutung Hadiastono; Aminudin Afandhi; Yusmani Prayogo (Universitas Brawijaya, 2013)
The obstacle in improving production of soybean is the attack of Cowpea mildmottle virus (CMMV). CMMV infection in the field by vector insect Bemisiatabaci. Entomopathogen fungi Lecanicillium lecanii is effective in killing insectsfrom homoptera ordo particularly Bemisia tabaci. Result of this study reveal thatthe higher conidia density in fungi L. lecanii, the more pathogenic this fungi inkilling B. tabaci thus CMMV intensity contaminated by vector insects is lower.Death of tested insects infected by fungi L. lecanii was highlighted with whitecolor mycelium colony that covers insect body. Conidia density of fungi L. lecaniiis effective in killing B. tabaci 108/ml with mortality rate 68.5% so that reduceCMMV attack intensity. The faster incubation period of fungi L. lecanii towardinsect would result lower ability of B. tabaci in spreading CMMV until reaching3.43%. The large seed soybean (Argomulyo) has trichoma density 127.18/cm2which is more vulnerable to be infected with CMMV compared with small seedsoybean (Wilis) which has trichoma density 182.83/cm2. Attack intensity ofCMMV in Argomulyo variety is reaching 29.89% while attack intensity in Wilisvariety only reach 23.94%. Reviewed from the efficacy of the fungi L. lecanii inkilling B. tabaci, the results of this study can be concluded 108/ml conidial densityis an effective dose. The use of small seed soybean varieties (Willis) with adensity of more tightly trichoma can pressess B. tabaci’s attack and CMMVinfection on soybean plants.Keywords: B. tabaci, Conidia density of L. Lecanii, Cowpea mild mottle virus(CMMV), Soybean plants